Horta's benchmark as a tool of Nursing teaching-learning: assistential convergent research - Juliana Helena Montezeli; Kriscie Kriscianne Venturi; Aida Maris Peres; Lilliana Maria Labronici; Mariluci Alves Maftum; Lillian Daisy Gonçalves Wolff (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
This is a qualitative research supported by the assistencial convergent modality that aimed to use Wanda Horta's referential with fifteen nursing students during Clinical Education in Semiology and Semiotchnical at a private college of Curitiba, and to verify the perception of these students concerning this trajectory. The students considered that this practice provided a vision of the patient as a whole, culminating in a theory-practice approach in the related disciplines and facilitating the care humanization. In addition, they emphasize that the systematization of nursing assistance based on Horta's benchmark reveals the importance of the nurse's work, since it outlines the knowledge of this category with greater precision, increasing the professional's performance perception and improving the quality of the nursing assistance.